ANALISIS MINAT GENERASI Z DAN MILENIAL PADA FILM ILEGAL DAN SITUS FILM LEGAL - Sony Dharmawan; Muhammad Farhan Ardian; Adrian Firdaus; Muhammad Dhika Ramadhan; Sugeng Santoso (Universitas Mercu Buana, 2021)
The film site is one of the creative industries in the film subsector. The film industry is not only a viewing medium for the public but also a source of economic income for a country, thereby increasing the country's economy. The purpose of this journal is to examine the influence of film sites on the Indonesian film subsector. The research method used is quantitative, the survey strategy uses a questionnaire with 100 respondents from the millennial generation and Z. From our discussion we get the results that the public's interest in choosing legal online film sites is very little compared to illegal film sites, because of the easy access and free given by illegal film sites even though they realize that such activity is something that is not justified.